Detrimental Effects of Testosterone Addition to Estrogen Therapy Involve Cytochrome P-450-Induced 20-HETE Synthesis in Aorta of Ovariectomized Spontaneously Hypertensive Rat (SHR), a Model of Postmenopausal Hypertension - Costa, Tiago J.; Ceravolo, Graziela S.; Echem, Cinthya; Hashimoto, Carolina M.; Costa, Beatriz P.; Santos-Eichler, Rosangela A.; Oliveira, Maria Aparecida; Jiménez-Altayó, Francesc; Akamine, Eliana H.; Dantas, Ana Paula; Carvalho, Maria Helena C. (Frontiers in Physiology, 2018)
Postmenopausal period has been associated to different symptoms such as hot flashes, vulvovaginal atrophy, hypoactive sexual desire disorder (HSDD) and others. Clinical studies have described postmenopausal women presenting HSDD can benefit from the association of testosterone to conventional hormonal therapy. Testosterone has been linked to development of cardiovascular diseases including hypertension and it also increases cytochrome P-450-induced 20-HETE synthesis which in turn results in vascular dysfunction. However, the effect of testosterone plus estrogen in the cardiovascular system is still very poorly studied. The aim of the present study is to evaluate the role of cytochrome P-450 pathway in a postmenopausal hypertensive female treated with testosterone plus estrogen. For that, hypertensive ovariectomized rats (OVX-SHR) were used as a model of postmenopausal hypertension and four groups were created: SHAM-operated (SHAM), ovariectomized SHR (OVX), OVX treated for 15 days with conjugated equine estrogens [(CEE) 9.6 µg/Kg/day/po] or CEE associated to testosterone [(CEE+T) 2.85 mg/kg/weekly/im]. Phenylephrine-induced contraction and generation of reactive oxygen species (ROS) were markedly increased in aortic rings from OVX-SHR compared to SHAM rats which were restored by CEE treatment. On the other hand, CEE+T abolished vascular effects by CEE and augmented both systolic and diastolic blood pressure of SHR. Treatment of aortic rings with the CYP/20-HETE synthesis inhibitor HET0016 (1 μM) reduced phenylephrine hyperreactivity and the augmented ROS generation in the CEE+T group. These results are paralleled by the increased CYP4F3 protein expression and activity in aortas of CEE+T. In conclusion, we showed that association of testosterone to estrogen therapy produces detrimental effects in cardiovascular system of ovariectomized hypertensive females via CYP4F3/20-HETE pathway. Therefore, our findings support the standpoint that the CYP/20-HETE pathway is an important therapeutic target for the prevention of cardiovascular disease in menopausal women in the presence of high levels of testosterone.